Implementasi Objektivitas dan Kode Etik Jurnalistik Dalam Pemberitaan Pelecehan Seksual Di Bahana Mahasiswa - Elfa Khairani; Suyanto (IAI Nasional Laa Roiba Bogor, 2024)
The increasing problem of sexual harassment at Universitas Riau has not escaped the attention of Bahana Mahasiswa's news coverage. As an independent campus media, it is necessary to examine how Bahana Mahasiswa applies the concept of Westerhal objectivity and journalistic ethics to such a sensitive issue. The concept of Westerhal objectivity is divided into two main points, namely factuality and impartiality. Meanwhile, the code of ethics serves as a moral and ethical foundation to ensure that a journalist consistently acts with social responsibility, based on the Journalistic Code of Ethics established by the Press Council and 29 press organizations on March 24, 2006, which consists of 11 articles. The purpose of this study is to examine how the application of Westerhal objectivity and the journalistic code of ethics is carried out in Bahana Mahasiswa's coverage of sexual harassment, with three specific news articles serving as the focus of the research. This study uses a qualitative method. The results of the research show that the three news articles adequately consider the points within the concept of Westerhal objectivity, particularly the aspect of factuality. However, in terms of impartiality, the news coverage is found to be inconsistent in achieving neutrality, specifically in avoiding bias and providing a fair space for all parties involved. Regarding the application of the journalistic code of ethics in the news coverage, several articles were found to be violated by Bahana Mahasiswa, namely articles 1, 2, 3, 4, 8, and 9. Based on the analysis of the journalistic code of ethics in the coverage of sexual harassment at Universitas Riau, Bahana Mahasiswa journalists did not fully demonstrate their commitment to adhering to the applicable Journalistic Code of Ethics.